2015
DOI: 10.1002/imhj.21514
|View full text |Cite
|
Sign up to set email alerts
|

A Quantitative Exploratory Evaluation of the Circle of Security‐parenting Program With Mothers in Residential Substance‐abuse Treatment

Abstract: Maternal substance abuse is a risk factor for child maltreatment, child attachment insecurity, and maladaptive social information processing. The aim of this study was to conduct a quantitative exploratory evaluation of the effectiveness of an attachment‐based parent program, Circle of Security‐Parenting (COS‐P; G. Cooper, K. Hoffman, & B. Powell, 2009), with a community sample of 15 mothers in residential treatment for substance abuse. Participants attended nine weekly group sessions and were given three meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 94 publications
(139 reference statements)
0
17
0
Order By: Relevance
“…The generalisability of the COS‐P program has been evident in previous studies that have concluded its efficacy in a number of settings and populations. For example, COS‐P has been successfully delivered to low‐income families in Head Start program (Cassidy et al., ); parents with infants under two years (Kohlhoff, Stein, Ha, & Mejaha, ); mothers in residential substance‐abuse treatment (Horton & Murray, ); and mothers with depressive symptoms (Maupin et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…The generalisability of the COS‐P program has been evident in previous studies that have concluded its efficacy in a number of settings and populations. For example, COS‐P has been successfully delivered to low‐income families in Head Start program (Cassidy et al., ); parents with infants under two years (Kohlhoff, Stein, Ha, & Mejaha, ); mothers in residential substance‐abuse treatment (Horton & Murray, ); and mothers with depressive symptoms (Maupin et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…They did find that mothers who participated in COS‐P reported fewer unsupportive responses to child distress than did control mothers, and intervention effects emerged for some child outcomes moderated by mothers’ attachment style or depressive symptoms, suggesting that further work should explore if COS‐P might benefit some dyads and not others. Two small studies ( n = 15 in each) have reported different benefits with different samples: increased parent reflective functioning, decreased caregiving helplessness and reduced anger and rejection toward the child in an Australian sample (Kohlhoff, Stein, Ha, & Mehaja, 2016), and improved emotion regulation and more positive parent attributions and discipline practices in American mothers with substance‐abuse problems (Horton & Murray, ). Limitations of these studies (with the exception of the studies by Cassidy et al., ; Cassidy et al., ) include very small sample sizes, no control conditions, and no follow‐up assessments to see if gains are maintained.…”
mentioning
confidence: 99%
“…Pilot data on the 20-wk CoS program collected from 20 mothers and their infants who were participating in Tamar's Children program, a 15-mo jail diversion residential program for pregnant nonviolent women who were substance-involved, suggested that these mothers demonstrated higher levels of sensitivity and had infants who exhibited more secure attachment post-treatment (76). At this time, researchers also are examining the feasibility of the 8-wk digital video disk-based program for mothers in residential drug treatment facilities (77,78), with initial studies suggesting that this program can promote improved parenting locus of control (78), parenting attributions, discipline practices (77), and emotion regulation (77,78).…”
Section: Attachment-based Parenting Interventionsmentioning
confidence: 99%